Statistics and probability in Spanish and Chilean pre-school and primary school textbooks (Edma 0-6: Educación Matemática en la Infancia, 2023)
This article seeks to identify the epistemic suitability, linked to statistics and probability, of the textbooks for Pre-school and Primary Education in Spain and Chile. Theoretical and methodological elements of Didactic Suitability are used, specifically, the epistemic facet. A content analysis of eight Chilean and Spanish textbooks is carried out. In both countries, the most frequent problem situation is the interpretation of representations and the construction of graphs and statistical tables. Situations linked to the study of probability are scarce and appear only in Spanish primary school textbooks.
Keywords: Textbooks; Early childhood education; Statistical education; Epistemic suitability